Fish biodiversity of the Vitória-Trindade Seamount Chain, southwestern Atlantic: an updated database. - Hudson T Pinheiro; Eric Mazzei; Rodrigo L Moura; Gilberto M Amado-Filho; Alfredo Carvalho-Filho; Adriana C Braga; Paulo A S Costa; Beatrice P Ferreira; Carlos Eduardo L Ferreira; Sergio R Floeter; Ronaldo B Francini-Filho; João Luiz Gasparini; et al. (PLoS ONE, 2015)
Despite a strong increase in research on seamounts and oceanic islands ecology and biogeography, many basic aspects of their biodiversity are still unknown. In the southwestern Atlantic, the Vitória-Trindade Seamount Chain (VTC) extends ca. 1,200 km offshore the Brazilian continental shelf, from the Vitória seamount to the oceanic islands of Trindade and Martin Vaz. For a long time, most of the biological information available regarded its islands. Our study presents and analyzes an extensive database on the VTC fish biodiversity, built on data compiled from literature and recent scientific expeditions that assessed both shallow to mesophotic environments. A total of 273 species were recorded, 211 of which occur on seamounts and 173 at the islands. New records for seamounts or islands include 191 reef fish species and 64 depth range extensions. The structure of fish assemblages was similar between islands and seamounts, not differing in species geographic distribution, trophic composition, or spawning strategies. Main differences were related to endemism, higher at the islands, and to the number of endangered species, higher at the seamounts. Since unregulated fishing activities are common in the region, and mining activities are expected to drastically increase in the near future (carbonates on seamount summits and metals on slopes), this unique biodiversity needs urgent attention and management.